Integrative Diniyah Curriculum in Formal Schools at Tebuireng Pesantren Jombang - Sholihuddin, Ahmad; Nidak, Khoiru (Didaktika Religia, 2023)
This article examines the incorporation of diniyah education into formal educational structures, with a particular focus on Tebuireng, with the objective of optimising the efficacy of diniyah learning institutions. A qualitative case study approach was employed, with particular focus on SMP A. Wahid Hasyim and MTs Salafiyah Syafi’iyah Tebuireng in Jombang. The data was gathered through the utilisation of documentation, interviews and observations, with the subsequent analysis conducted in accordance with the principles established by Miles and Huberman. The findings indicate that the integration of the madrasah diniyah pondok pesantren curriculum into formal educational institutions is achieved through the adaptation of grades 7, 8, and 9, with the curriculum and instructional hours tailored to align with the proficiency level of the students. The ‘Ula’ classes are incorporated into the major and junior/senior high school levels, while the ‘Wustha’ classes are integrated into the minor levels. At the middle school level, the Wustha curriculum is aligned with the major level, while the ‘Ulya class is integrated into the minor level. At the MA level, the ‘Ulya and Wustha classes are merged in a 50:50 ratio. The development of teachers is facilitated through the implementation of debriefing, academic activities, and coaching. The provision of supervision and the Subject Teacher Conference (MGMP) facilitate direct feedback, enabling challenges to be addressed and the quality of diniyah education to be enhanced through HR supervision and lesson restructuring.